Background of The Board of Director and Financial Intermediary: Does It Contribute to The Performance of Islamic Banks? - Rahmawati, Alvi (Maliki Islamic Economics Journal, 2023)
This study aims to examine the effect of women leadership, education level, financing and investment on the profitability of Islamic banks. The type of data used is secondary data in the form of annual reports of Islamic banks for the 2016-2020 period. Data collection was carried out using purposive sampling technique so that the sample obtained for research was 12 Islamic banks. The analytical tool used in this panel data regression with dummy variables is e-views 10 software. The results showed that partially financing and investment have a positive and significant effect on the profitability of Islamic banks, while women leadership and education level have no effect on profitability. Simultaneously, women's leadership, education level, financing and investment have an influence on profitability. Then based on the results of the determination test shows that the independent variables in the form of women's leadership, education level, financing and investment are able to explain the dependent variable profitability by 99%, while the other 1% is explained by other variables not mentioned in this study.